Impact of Destination Image on the Loyalty of International Tourists to Hanoi - Hương, Hoàng Thị Thu; Mạnh, Nguyễn Văn (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 31 No 5E, 2015)
Abstract: The paper aims at enhancing the competitiveness of tourism destinations by taking into account the point of view of tourists. Founded on customer-based brand equity (Keller, 2003 [1]; Aaker, 1991 [2]), our purpose is to build a linkage between tourism destination image and a tourist’s loyalty in their selection of a tourist destination (revisit and/or recommendation to other people), in order to better understand the role of branding tourism destinations. This paper carried out a survey of international tourists who selected Hanoi - Vietnam as their holiday destination. The results indicated that international tourists to Hanoi considered Hanoi’s image as being significant in determining their loyalty. The findings further indicated that the authority needs to expand Hanoi tourism to encourage the current tourists to revisit Hanoi one more time or at least that they recommend Hanoi positively to other people by using destination branding methods. Keywords: Destination image, customer-based brand equity, tourist behaviour, tourists’ behavioral intentions.